Method for Determining Longitudinal Stiffness of Combined Double Thin-Walled Pier Based on Train-Track-Bridge Interaction - Hui Fang; Zhaowei Chen (Advances in Civil Engineering)
Combined double thin-walled pier is a new kind of pier adopted in the urban transit system in China, whose longitudinal stiffness cannot be determined by adopting traditional methods. Aiming at this practical issue, this work proposed an alternative method for determining the longitudinal stiffness of the combined double thin-walled pier based on the train-track-bridge interaction. Primarily, the relationship between longitudinal stiffness of the pier and rail stress is underlined, based on which the proposed methodology is described in detail. Finally, a case study is conducted to validate the effectiveness of the proposed method. Results show that the train-track-bridge dynamic interaction theory is effective in determining the longitudinal stiffness of the newly designed and special pier. Rail stress and longitudinal displacement of pier top exceed their limit values with the change of pier longitudinal stiffness. The dynamic stress and thermal stress of rail are the two most important indicators in determining pier longitudinal stiffness, which should be paid attention to in practical engineering.